Neutralizing antibodies against Simbu serogroup viruses in cattle and sheep, Nigeria, 2012–2014 - Daniel Oluwayelu (BMC Veterinary Research, 2018)
Abstract Background Simbu serogroup viruses of the Orthobunyavirus genus (Family Peribunyaviridae) include teratogenic pathogens that cause severe economic losses, abortions, stillbirths and congenital abnormalities in ruminants worldwide. Although they were initially isolated from ruminants and Culicoides biting midges about five decades ago in Nigeria, there is no current information on their prevalence and geographical distribution despite reports of abortions and congenital malformations in the country’s ruminant population. Here, apparently healthy cattle and sheep obtained from eight states in the three major vegetation zones of Nigeria were screened for the presence of specific neutralizing antibodies against Schmallenberg virus (SBV), Simbu virus (SIMV) and Shamonda virus (SHAV). Results Using a cross-sectional design, 490 cattle and 165 sheep sera were collected between 2012 and 2014 and tested by a commercial SBV ELISA kit which enables the detection of antibodies against various Simbu serogroup viruses. The seropositivity rates for cattle and sheep were 91.2% and 65.4%, respectively. In cattle, there was no association between ELISA seropositivity and vegetation zone. However, the prevalence of anti-Simbu serogroup antibodies was significantly higher in Ebonyi State compared to other states in the rainforest vegetation zone. The seroprevalence was significantly higher in sheep obtained from live animal markets compared to farms (OR = 5.8). Testing of 20 selected ELISA-positive sera by serum neutralisation test showed that all were positive for one or more of SBV, SIMV and SHAV with the highest titres obtained for SHAV. Antibodies to SBV or a closely related virus were detected in the Sudan savannah and rainforest zones, anti-SIMV antibodies were detected only in the rainforest zone, while anti-SHAV antibodies were found in the three vegetation zones. Conclusion The findings of this study reveal that following the early isolation of Simbu serogroup viruses in Nigeria in the 1960s, members of this virus group are still circulating in the country. Specifically, SBV, SIMV and SHAV or closely related viruses infect cattle and sheep across the three vegetation zones of Nigeria suggesting that insect vector activity is extensive in the country. The exact vegetation zone where the animals became exposed to the viruses could, however, not be determined in this study.